Advances in immunotherapy for bladder cancer and clinical practice of next-generation sequencing - Ning, Wei; Chang, Pengkang; Zheng, Ji; Chen, Wei (Frontiers in Immunology, 2026)
Bladder cancer kills nearly 170,000 people worldwide each year. Over the past 4 decades, the systematic treatment of metastatic and locally advanced bladder cancer has mainly consisted of platinum-based chemotherapy. In the last 10 years, the development of next-generation sequencing have led to rapid characterization of whole-genome sequencing of bladder cancer, which gives us a better understanding of the pathogenesis of bladder cancer. Based on indications of high mutation burden, and microsatellite instability-high/deficient mismatch repair, immune checkpoint inhibitors have been studied in metastatic and locally advanced bladder cancer as well as bladder-sparing, and shows a good response in these specific indications. Besides, clinically significant expressed molecular targets are used to develop cancer targeted drugs, such as fibroblast growth factor receptor inhibitors and antibody-drug coupling agents. The exploration of molecular characteristics and subtypes of bladder cancer and the development of new drugs and treatment strategy have also stimulated more clinical studies of bladder cancer. Here, we review advances in the treatment of bladder cancer and clinical practice of next-generation sequencing, highlight important advances in immunotherapy for bladder cancer, preliminarily summarize molecular features of bladder cancer for clinical practice, and came up with direction for future treatment development.